2002
DOI: 10.1097/01.asn.0000031701.53792.54
|View full text |Cite
|
Sign up to set email alerts
|

A Monocyte Chemoattractant Protein-1 (MCP-1) Polymorphism And Outcome After Renal Transplantation

Abstract: Abstract. Among the factors modulating transplant rejection and cardiovascular disease, chemokines and their respective receptors deserve special attention. In this respect, increased expression of MCP-1 and the corresponding receptor CCR2 have been demonstrated in renal transplant rejection and coronary artery disease. The impact of the MCP-1-2518G and CCR2-64I genotypes on renal allograft function was investigated in 232 patients who underwent transplantation over an 11-yr period. Genomic DNA was genotyped u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 30 publications
5
42
2
Order By: Relevance
“…CCR2V64I mutation had no effect on kidney, liver or heart graft failure 38,68,69 . However a significant reduction in the risk of acute renal transplant rejection was found in recipients who possessed the CCR2-64I allele 70 .…”
Section: Other Diseasesmentioning
confidence: 90%
See 1 more Smart Citation
“…CCR2V64I mutation had no effect on kidney, liver or heart graft failure 38,68,69 . However a significant reduction in the risk of acute renal transplant rejection was found in recipients who possessed the CCR2-64I allele 70 .…”
Section: Other Diseasesmentioning
confidence: 90%
“…Considering involvement of leukocyte infiltration in allograft rejection, detection of genetic markers for CCL2 upregulation could also be helpful for predicting the outcome of transplantation. In this context, Kruger et al showed that MCP-1-2518 GG genotypes of kidney graft recipient reduce long-term graft survival 38 . On the other hand, Schroppel et al genotyped liver transplant recipients for MCP-1-2518 SNP and failed to show any association with the incidence of acute rejection episodes or long-term liver graft survival 39 .…”
Section: Other Diseasesmentioning
confidence: 99%
“…The À2578 G polymorphism in the CCL2 distal promoter is an example of a functional promoter polymorphism that associates with disease pathogenesis, correlates with protein levels in vivo and affects reporter gene expression 3,9,[11][12][13][14][15][16]19 (Figure 1). In the present study, we have investigated the À2578 polymorphism in an astrocytic cell line to model the influence of this site in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other studies demonstrated that the guanine polymorphism increased the levels of CCL2 produced in cultured peripheral blood mononuclear cells, monocytes and hepatic stellate cells providing evidence that the polymorphism regulates CCL2 expression in the context of the endogenous promoter. [11][12][13][14][15][16] Almost 6 years ago, a provocative study associated the À2578 G allele with protection against initial HIV infection; however, once individuals were infected, they exhibited a more rapid progression to acquired immune deficiency syndrome and a 4.5-fold increased chance of developing HIV-D compared to individuals carrying the ancestral À2578 A allele. 9 Preliminary molecular analysis in this study suggested that the region encompassing the À2578 polymorphism shared homology with an interferon-stimulated response element (ISRE) and that the transactivator interferon regulatory factor (IRF)-1 bound the À2578 A allele with higher affinity than the À2578 G allele.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation